2019
DOI: 10.1186/s12863-019-0806-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cage and floor rearing system on the factors of antioxidant defense and inflammatory injury in laying ducks

Abstract: BackgroundCage-rearing in laying ducks, as a novel rearing system, not only fundamentally solves the pollution problem of the duck industry and improve bio-safety and product quality but also exhibits more benefits by implementing standardized production compared with the floor-rearing. Of course, this system also brings some welfare problems and stress injuries to layers due to lack of water environment and limited activities in the cages. However, the effects on the factors of antioxidant defense and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…According to previous study, cage-rearing stress gradually subsides after the 4 th day (ZHANG et al 2019). Herein, there was a decrease in the expression of the CRH gene although there was no significant difference in the expression of the ACTH gene (Proopiomelanocortin, POMC).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…According to previous study, cage-rearing stress gradually subsides after the 4 th day (ZHANG et al 2019). Herein, there was a decrease in the expression of the CRH gene although there was no significant difference in the expression of the ACTH gene (Proopiomelanocortin, POMC).…”
Section: Discussionmentioning
confidence: 69%
“…Previous research showed that cage-rearing can cause endoplasmic reticulum stress and lead to liver injury in ducks. It was also reported that there was an increase in the expression levels of inflammation-related factors and immune-related genes (ZHANG et al 2019). It is noteworthy that changes in the external environment affect the transcriptome of an organism (KRISHNAN et al 2020;WANG et al 2020;XU et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed these parameters were coherently lower in NRS ducks at different ages, demonstrating NRS was better for duck liver health despite the lipid deposition enhancement and liver developmental retardation. And this also showed an advantage over CRS, as ducks suffered liver injury once they were just put into cages [35]. Furthermore, antioxidant capacity prevents cell damage from free radicals and other reactive oxygen species (ROS) to avoid oxidative stress (the imbalance between ROS and antioxidants) [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of MDA and activities of SOD, GSH-Px are effective indicators to re ect the antioxidant status of ducks [38,39]. A study on Shaoxing ducks showed rearing systems did not have signi cant impacts on the activity of MDA, SOD, CAT, T-AOC, and GSH-Px in the liver [35]. Another study though only determined the total antioxidant capacity (T-AOC) in serum, results showed no signi cant difference between FRS and NRS [5].…”
Section: Discussionmentioning
confidence: 99%